2016
DOI: 10.1002/rob.21652
|View full text |Cite
|
Sign up to set email alerts
|

Development and Testing of a Control System for the Automatic Flight of Tethered Parafoils

Abstract: This paper presents the design and testing of a control system for the robotic flight of tethered kites. The use of tethered kites as a prime mover in airborne wind energy is undergoing active research in several quarters. There also exist several additional applications for the remote or autonomous control of tethered kites, such as aerial sensor and communications platforms. The system presented is a distributed control system consisting of three primary components: an instrumented tethered kite, a kite cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The challenges to attach reliable instrumentation to the canopy fabric make in-flight experimental measurements either impossible or extremely difficult [6]. While recent efforts focusing on control and guidance have successfully used in-canopy motion sensors [9,10,12,26], the in-flight measurement of the airfoil aerodynamic characteristics remains a challenge. None of these works, however, attempted to use outer-inner local pressure-differential analysis as an alternative to the classic external pressure coef-ficient assessments.…”
Section: Structural Aspectsmentioning
confidence: 99%
“…The challenges to attach reliable instrumentation to the canopy fabric make in-flight experimental measurements either impossible or extremely difficult [6]. While recent efforts focusing on control and guidance have successfully used in-canopy motion sensors [9,10,12,26], the in-flight measurement of the airfoil aerodynamic characteristics remains a challenge. None of these works, however, attempted to use outer-inner local pressure-differential analysis as an alternative to the classic external pressure coef-ficient assessments.…”
Section: Structural Aspectsmentioning
confidence: 99%
“…The non-reversing pumping-mode AWE system employing a kite or a glider for harnessing the wind energy is the focus of this paper [5]. Non-reversing pumping mode AWE systems have been initially developed at the University of Limerick, Ireland [5][6][7]. In this type of pumping mode AWE system, a kite or glider is tethered to a ground station consisting of a tether drum coupled to a generator and a fractional scale recovery motor.…”
Section: Introductionmentioning
confidence: 99%
“…23 All these small-scale infrastructures involve sensor fusion setups and algorithms mostly targeted (but not limited) to the dynamic characterization and closed-loop control design of AWE systems. [24][25][26][27][28][29] Most of them included onboard equipment like an inertial measurement unit (IMU), global navigation satellite system (GNSS) receivers, load cells, and line angle sensors, among others. It was demonstrated that line angle sensors jeopardized the estimations due to tether sagging and tether dynamics when compared with range sensors.…”
mentioning
confidence: 99%